Econometric models and economic forecasts - Pindyck, Robert S (McGraw-Hill, 2020)
Single-equation regression models (introduccion to the regression model; elementary statistics: a review; two-variable regression model; multiple regression model; using the multiple regression model; serial correlation and heteroscedasticity; instrumental variables and model specification; forecasting with a single-equation regression model; single-equation estimation: advanced topics; models of quantitative choice); Multi-equation simulation models (simultaneous-equation estimation; introduction to simulation models; dinamic behavior of simulation models); The-series models (smoothing and extrapolation of timer series; properties of stochastic time series; linear time-series models; estimating and checking time-series models; forecasting with time-series models; applications of time-series models).